«Det var nogen vildtsmak av hans ånde»: Thomas Glahn og det samiske rundt Sirilund - Lødemel, Andreas (Nordlit, 2016)
Often when the theme of Hamsun and the Sami is discussed, the focus is on the nation building structures and negative generalizations contained in Growth of the Soil (1917). Hamsun’s earlier novel Pan (1894) is sometimes mentioned in passing as an example of a more positive or neutral attitude towards the Sami. This essay adds some nuance to this narrative by examining the motif of the Sami in Pan with a line drawn to the novel Rosa (1908). The presence of the Sami is limited in Pan. Hamsun relegates them to the relatively inhospitable mountains surrounding the coastal village of Sirilund. When they do appear, Glahn’s interactions with the Sami play an interesting part in the story of the porous identity of this narrating main character. In Rosa, which like Pan is set in Sirilund, Edvarda remembers Glahn, and she makes a symbolic link between his sexual power and the Sami. Later, in what is for Hamsun an uncharacteristically sexually explicit scene between Edvarda and the Sami character Gilbert Lap, we can find an echo of the famous scene from Pan where the goat god makes his only appearance, mocking Glahn through silent laughter.